2020
DOI: 10.1155/2020/1704879
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and Risk of Dementia in Patients with Late-Onset Depression: A Population-Based Cohort Study

Abstract: Background. Late onset depression (LOD) often occurs in the context of vascular disease and may be associated with risk of dementia. Aspirin is widely used to reduce the risk of cardiovascular disease and stroke. However, its role in patients with LOD and risk of dementia remains inconclusive. Materials and Methods. A population-based study was conducted using data from National Health Insurance of Taiwan during 1996–2009. Patients fulfil diagnostic criteria for LOD with or without subsequent dementia (inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Twelve included studies were cohort studies (Zandi and Breitner, 2001 ; Jonker et al, 2003 ; Kang and Grodstein, 2003 ; Nilsson et al, 2003 ; Cornelius et al, 2004 ; Arvanitakis et al, 2008 ; Szekely et al, 2008 ; Kern et al, 2012 ; Kelley et al, 2015 ; Chang et al, 2016 ; Wichmann et al, 2016 ; Yang et al, 2020 ) and three RCTs (Kang et al, 2007 ; Matsumoto et al, 2020 ; Ryan et al, 2020 ). Studies were conducted in the US (Zandi and Breitner, 2001 ; Kang and Grodstein, 2003 ; Kang et al, 2007 ; Arvanitakis et al, 2008 ; Szekely et al, 2008 ; Kelley et al, 2015 ; Wichmann et al, 2016 ), Europe (Jonker et al, 2003 ; Nilsson et al, 2003 ; Cornelius et al, 2004 ; Kern et al, 2012 ), and Asia (Chang et al, 2016 ; Matsumoto et al, 2020 ; Yang et al, 2020 ). However, only one RCT (Ryan et al, 2020 ) included both American and Australian data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve included studies were cohort studies (Zandi and Breitner, 2001 ; Jonker et al, 2003 ; Kang and Grodstein, 2003 ; Nilsson et al, 2003 ; Cornelius et al, 2004 ; Arvanitakis et al, 2008 ; Szekely et al, 2008 ; Kern et al, 2012 ; Kelley et al, 2015 ; Chang et al, 2016 ; Wichmann et al, 2016 ; Yang et al, 2020 ) and three RCTs (Kang et al, 2007 ; Matsumoto et al, 2020 ; Ryan et al, 2020 ). Studies were conducted in the US (Zandi and Breitner, 2001 ; Kang and Grodstein, 2003 ; Kang et al, 2007 ; Arvanitakis et al, 2008 ; Szekely et al, 2008 ; Kelley et al, 2015 ; Wichmann et al, 2016 ), Europe (Jonker et al, 2003 ; Nilsson et al, 2003 ; Cornelius et al, 2004 ; Kern et al, 2012 ), and Asia (Chang et al, 2016 ; Matsumoto et al, 2020 ; Yang et al, 2020 ). However, only one RCT (Ryan et al, 2020 ) included both American and Australian data.…”
Section: Resultsmentioning
confidence: 99%
“…However, only one RCT (Ryan et al, 2020 ) included both American and Australian data. Two of the studies were from Taiwan (Chang et al, 2016 ; Yang et al, 2020 ) and extracted their data from the National Health Insurance Research Database, but the investigators used different study populations and separate cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the four studies on all-cause dementia, three reported statistically significant results and only the study of Kern et al, 39 which was underpowered (n=41 cases), showed no statistical differences between LDASA users and non-users regarding the 5-year risk of dementia. None of the 4 individual studies is comparable to our study populations from the UK Biobank and ESTHER (general population, age ≥55) because they included either only women, 39 twins aged 80 years or older, 41 patients with late-onset depression 42 or type 2 diabetes patients. 40…”
Section: Discussionmentioning
confidence: 99%
“…7 Overall, a meta-analysis of 8 studies indicated that the use of any dose of ASA did not significantly decrease the risk of developing dementia (pooled relative risk (RR) [95% CI]: 0.94 [0.77 to 1.16]. However, when the authors restricted the meta-analysis to 4 studies with LDASA exposure and the outcome all-cause dementia 39-42 and 2 studies with LDASA exposure and the outcome AD, 40 41 LDASA use showed a protective effect against all-cause dementia (pooled RR [95% CI]: 0.82 [0.71 to 0.96]) and AD (pooled RR [95% CI]: 0.54 [0.33 to 0.89]). Among the four studies on all-cause dementia, three reported statistically significant results and only the study of Kern et al, 39 which was underpowered (n=41 cases), showed no statistical differences between LDASA users and non-users regarding the 5-year risk of dementia.…”
Section: Discussionmentioning
confidence: 99%